0970 Longitudinal Study Of Infant Sleep Problems And Influencing Factors. (27th May 2020) - Zhou, Z; Wang, N
Abstract: Introduction: To investigate the sleep problems and influence factors in infants at the age of 1 month and 6 months through longitudinal questionnaire survey. Methods: 600 healthy infants aged 1 month were selected from May to August 2014 from Chongqing health center for women and children. A self-made sleep questionnaire was used to investigate the infants's sleep at the age of 1 month and 6 months respectively. Logistic regression model was used to analyze the correlation between sleep problems and factors. Results: The incidence of nigt-waking, difficulty in falling asleep and night crying at 1 month of age were 30%, 17% and 14.1%, respectively, and at 6 months were 7.3%, 9.3% and 13.1%, respectively. Results of the Logistic regression analysis model of sleep problems of infants at 1 month old were: 1. body length grade, baby touch, sleep alone, putting the infants back into bed after being picked up and quiet, night feeding were the protective factors of night-waking, while diaper changing is the risk factor; 2.body length grade, listening to music, orderly bedtime routine, comforting without holding and putting the infants back into bed after being picked up and quiet were protective factors for difficulty in falling asleep, while diaper changing is the risk factor; 3. listening to music, orderly bedtime routine, watching and waiting, holding until sleep were all protective factors of night-crying. Logistic regression model analysis results of sleep problems of infants aged 6 months were: 1. The risk factors of night-waking include putting the infants back into bed after being picked up and quiet, holding the infants until falling asleep, diapers changing, and parent-children interaction before bedtime. 2. Listening to music and sleeping alone in a bed were protective factors for difficulty in falling asleep. 3. Touching, orderly bedtime routine and comforting without holding are protective factors of night-crying. Conclusion: Sleep problems in infants are common and decrease with age. The factors of sleep problems at the age of 1 and 6 months are different, Targeted prevention are beneficial to the prevention of infant sleep problems. Support: Chinese center for disease control and prevention grant